Pygmy grasshoppers of the genus Formosatettix Tinkham, 1937 (Orthoptera: Tetrigidae: Tetriginae). Issue 17 (11th May 2019) - Wei, Shi-Zhen; Deng, Wei-An; Lu, Xiang-Yi
ABSTRACT: Formosatettix serrifemora Deng sp. nov., Formosatettix zhejiangensis Deng sp. nov. and Formosatettix guposhanensis Deng sp. nov. are described with detailed illustrations of external morphology. New synonymy is proposed: Formosatettix tianmushanensis Zheng and Li = Formosatettix xiai Zheng, Shi and Yin, syn. nov. An updated key to species of the genus is given. http://www.zoobank.org/urn:lsid:zoobank.org:pub:D64FA763-EBA7-453C-9D76-7209F5659478